Nástin mediálního diskursu o Janově: Kriticko-diskursivní přístup - Petr Vašát (AntropoWebzin, 2010)
This paper focus on a media presentation of events related to the situation that is generally called as social tension in Janov. The tool of this aim is a specific qualitative research method - critical discourse analysis. The method allows combine classical textual and intertextual analysis. There are identified two ideological practices in the Janov media discourse: (1) construction of Gypsy ethnic category, (2) construction of socially excluded locality. These ideological practices are supported by specific textual features and their concrete discursive expressions, both outlined in the analysis.